Radiological Evaluation of Renal Masses - Boricha, Ankita; Jethva, Maulik; Tarafdar, Devasish; Trivedi, Anjana; Solanki, Chirag (Asian Journal of Medical Radiological Research, 2021)
Renal masses are a broad group of lesions from benign to malignant. The goal of imaging is to differentiate malignant renal masses from benign masses. This study intends to evaluate the role of radiological modalities like X-ray, IVP, USG, CT Scan, MRI, Interventional procedures etc. in the evaluation of renal masses and to review the imaging spectrum of renal masses on the various imaging modalities and also decide radiological investigation approach for renal masses. The present study is carried out on 50 cases of renal masses, in the duration of two years. Most common affected Age group is 40-50 years. Mostly the incidence is higher in males with benign renal masses are commoner. Most common malignant renal masses are Renal cell carcinoma, amongst them Clear cell RCC are most common. Ultrasound was 100% accurate in diagnosing cystic lesion. CT Scan is more accurate than USG for detection and characterization of the benign and malignant solid renal masses.